Use-centred design of medical and healthcare technology: a pilot study of field tests as a development tool. (1st January 2011) - Karlsson, I.C. MariAnne; Engelbrektsson, Pontus; Larsson, Lena E.; Pareto, Lena; Snis, Ulrika; Berndtsson, Bo; Svensson, Lars
The purpose of the project has been to develop a process through which users, staff as well as patients, can be involved in field evaluations of medical and healthcare technology. Interviews with different stakeholders and the experiences from four case studies have led to the following conclusions. Users have the potential to act as active evaluators rather than passive subjects or participants only. However, user involvement in field evaluations must be supported by a formation of facilitators or 'door openers' to the healthcare organisation, moderators enhancing the dialogue between developers and users, and mentors for the users acting as evaluators.